Sea ice resource selection models for polar bears in the Barents Sea subpopulation. Issue 4 (15th June 2017) - Lone, Karen; Merkel, Benjamin; Lydersen, Christian; Kovacs, Kit M.; Aars, Jon
Abstract : The extent, thickness and age of Arctic sea ice has dramatically declined since the late 1990s, and these trends are predicted to continue. Exploring the habitat use of sea‐ice‐dependent species can help us understand which resources they use and how their distribution responds to a changing environment. The goal of this study was to develop predictive models of the habitat use of an Arctic apex predator. Polar bear Ursus maritimus habitat use in the Barents Sea subpopulation was modelled with seasonal resource selection functions (RSFs) using satellite‐linked telemetry data from 294 collars deployed on female polar bears between 1991 and 2015. Polar bears selected habitat in the Marginal Ice Zone, with a preference for intermediate sea ice concentrations (40–80%). They spent most time in areas with relatively short travel distances to 15 or 75% ice concentration, and during spring and autumn they exhibited a preference for sea ice areas over the continental shelf or over shallower bathymetry). Predictions of the distribution of polar bears in the Barents Sea area can be made for specific sea ice scenarios using these models. Two such predictive distribution maps based on the autumn seasonal model were made and validated against two independent polar bear survey datasets collected in August 2004 and August 2015. The distribution of optimal polar bear habitat has shifted strongly northwards in all seasons of the year during the 25 yr study period.